The enigmatic Bartholomew Lloyd alias Frederick Dalton: identity and mobility during the gold rush era in New South Wales. Issue 2 (3rd April 2019) - Crabb, Peter; Dalton, Brendan; Craig, Hugh; Antonia, Alexis
Abstract: This is the third article recording our investigations of the authorship and authors of Sydney Morning Herald articles on the mid-nineteenth-century goldfields of New South Wales. Whereas the first two focused on the identification of the anonymous author and his inexplicable disappearance, this article explores the implications of our serendipitous discovery of the author's alter ego. The man we knew as Dalton was actually Bartholomew Lloyd, who had had a very different previous life and a very different ancestry. And it was a name and life he returned to after nearly 30 years. But our story of an eminently respectable citizen who disappeared twice became much more. It took us beyond primarily issues of authorship attribution to important aspects of life in the colonial world of the second half of the nineteenth century. The period was one of extraordinary mobility, internationally and nationally. Mobility facilitated changes and concealment of identity, with their associated issues of responsibility and questionable morality. The story of Lloyd/Dalton is also yet another illustration of the ever-changing nature of historical knowledge.